Implementasi Media Interaktif Games Digital Dalam Meningkatkan Kualitas Hasil Belajar Pendidikan Agama Islam di SMP An-Nizam - Azmia, Irza; Fanreza, Robie (Yayasan Rahmat Islamiyah, 2024)
Today's education sector has profited immensely from changing circumstances, scientific discoveries, and information and communication technology improvements. The fourth industrial revolution and digitization have brought about a rapid development of the current period. In spite of this, there are still teachers who do not know how to use technology to improve student learning. As a result, learning outcomes are ineffective and pupils become bored.Â There are lots of educational video game apps available for students to use. One of the advances in learning utilizing modern learning media is Kahoot, an interactive internet application used as a teaching tool in schools that shows quizzes as online games. The study aims to ascertain the following: (1) how the Kahoot application is used in the learning process; (2) how students respond when using Kahoot media in the learning process; and (3) how the quality of student learning outcomes compares before and after the Kahoot application is applied.